Reclassification of Theileria annae as Babesia vulpes sp. nov. - Baneth, Gad; Florin-Christensen, Mónica; Cardoso, Luís; Schnittger, Leonhard (2017)
Background: Theileria annae is a tick-transmitted small piroplasmid that infects dogs and foxes in North America and Europe. Due to disagreement on its placement in the Theileria or Babesia genera, several synonyms have been used for this parasite, including Babesia Spanish dog isolate, Babesia microti-like, Babesia (Theileria) annae, and Babesia cf. microti. Infections by this parasite cause anemia, thrombocytopenia, and azotemia in dogs but are mostly subclinical in red foxes (Vulpes vulpes). Furthermore, high infection rates have been detected among red fox populations in distant regions strongly suggesting that these canines act as the parasite’s natural host. This study aims to reassess and harmonize the phylogenetic placement and binomen of T. annae within the order Piroplasmida. Methods: Four molecular phylogenetic trees were constructed using a maximum likelihood algorithm based on DNA alignments of: (i) near-complete 18S rRNA gene sequences (n = 76 and n = 93), (ii) near-complete and incomplete 18S rRNA gene sequences (n = 92), and (iii) tubulin-beta gene sequences (n = 32) from B. microti and B. microti-related parasites including those detected in dogs and foxes. Results: All phylogenetic trees demonstrate that T. annae and its synonyms are not Theileria parasites but are most closely related with B. microti. The phylogenetic tree based on the 18S rRNA gene forms two separate branches with high bootstrap value, of which one branch corresponds to Babesia species infecting rodents, humans, and macaques, while the other corresponds to species exclusively infecting carnivores. Within the carnivore group, T. annae and its synonyms from distant regions segregate into a single clade with a highly significant bootstrap value corroborating their separate species identity. Conclusion: Phylogenetic analysis clearly shows that T. annae and its synonyms do not pertain to Theileria and can be clearly defined as a separate species. Based on the facts that T. annae and its synonyms have not been shown to have a leukocyte stage, as expected in Theileria, do not infect humans and rodents as B. microti, and cluster phylogenetically as a separate species, this study proposes to name this parasite Babesia vulpes sp. nov., after its natural host, the red fox V. vulpes.